Estimation of reservoir temperature and analysis of the mechanism of origin of a granite dome-controlled geothermal system in the western Wugongshan area, southeast China - Wang, Luyao; Liu, Kai; Zhang, Shouchuan; Zhang, Yaoyao; Jia, Wuhui; Yu, Tingxi; Guo, Junhan (Frontiers in Earth Science, 2023)
The escalating issues of worldwide energy scarcity and environmental contamination have brought geothermal resources into the spotlight as a sustainable and eco-friendly energy alternative. The circum-Wugongshan geothermal belt has abundant geothermal resources at a medium-low temperature, offering significant potential for development and utilization. In this study, samples of geothermal groundwater, cold spring water, and surface water were collected from the western Wugongshan area. Hydrochemical and thermodynamic methods were used to estimate the reservoir temperature and analyze its mechanism of origin. The results of these analyses indicated that, in terms of hydrochemical characteristics, most geothermal groundwater samples were Na-HCO3 and Na-SO4, while cold spring and surface water samples were Na-HCO3 and Ca-HCO3, respectively. Quartz and multicomponent geothermometers provided the most reliable estimations of reservoir temperatures, ranging from 64.8°C to 93.4°C. The circulation depth of geothermal water was found to range from 1729.3 m to 2,292.5 m. A mixing model indicated that shallow cold water was blended at a rate of 62.1%–78.8%. The δD and δ18O values validated the conclusion that the geothermal water originates from atmospheric precipitation, with recharge elevations varying between 503.1 m and 1,375.6 m. Based on the above analysis, a conceptual model is proposed to illustrate the mechanism of geothermal groundwater genesis.